The Evolving Role of Dental Assistants in Modern Dentistry: A Systematic Review of Responsibilities, Challenges, and Impact on Patient Care - Loolah Mohammed al jarshi; Abrar Abdullah Alharbi; Huda Ali Albishi; Haneen Jafar Hawsawi; Samah Omar Alhousah; Afnan Abdulltif M Abdulltif; Khadijah Abdulqader Saad; Khadejah Yousef Al hosawi (The Bioscan, 2025)
The role of dental assistants in modern dentistry has evolved significantly, encompassing a broad spectrum of clinical, administrative, and technological responsibilities. This systematic review examines the expanding scope of dental assistants’ duties, the challenges they face, and their impact on patient care and dental practice efficiency. The findings highlight that dental assistants contribute to improved workflow, reduced chair time, and enhanced patient satisfaction through their involvement in chairside assistance, infection control, radiography, and patient education. However, challenges such as occupational stress, limited career advancement opportunities, and workforce shortages persist, affecting retention and job satisfaction. Technological advancements, including the integration of digital tools and artificial intelligence, are reshaping dental assisting, emphasizing the need for continuous education and policy improvements. This review underscores the importance of recognizing and supporting dental assistants’ roles to optimize healthcare outcomes and enhance the efficiency of dental practices.